DWIPURWA REDUPLCATION OF MALAY IN RIAU DISTRICT OF RENGAT - Riri Amanda Fitriana Amanda Fitriana; Auzar '; Mangatur Sinaga Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research aim to to know form, explaining process, and analyse meaning which there are in Malay dwipurwa reduplication of Riau in District of Rengat. This Research represent research qualitative. Object in this research the form of words written oral the than behavior and people perceived for this research. this Research data obtained by using interview technique, record, record-keeping of field, and documentation. Result of this research in the form of form of dwipurwa reduplication, forming process, and the meaning. Pursuant to its for, there are 40 word of dwipurwa reduplcation without afiks and 24 word of dwipurwa reduplication with afiks. Pursuant to process, dwipurwa reduplication pass three step that is natural headword of reduplication full of, happened syllable dissipation, and happened change of phoneme. Pursuant to its meaning, meaning which implied in dwipurwa reduplication at Malay of Riau in District of Rengat found by counted nine kinds of, representing aliance of meaning of reduplication noun, verb. reduplication, adjective reduplication, and number word reduplication.Keys words: Dwipurwa Reduplication, District of Rengat